Propuesta de aplicación virtual de la técnica collage en un grupo de enfoque, con el propósito de disminuir el ausentismo, el tiempo y los costos que implica hacerlo de forma presencial - Martínez Espínola, Edgar Eliezer (2018)
The focus group provides a deeper and extensive idea of the experiences and motivations of consumers by the interactions among them; this technique is often supported with others as collage which aim is to obtain information that consumers do not show if they are asked in a direct way. Due to social media, the way that people interact has changed from personal to virtual. For that reason, this study proposes to apply the collage technique in focus group using ICT, and it tries to reduce the disadvantages of doing it in person.